2001
DOI: 10.1086/322631
|View full text |Cite
|
Sign up to set email alerts
|

Improving Efficacy of Antifungal Therapy by Polymerase Chain Reaction–Based Strategy among Febrile Patients with Neutropenia and Cancer

Abstract: Early detection of fungal infections in and corresponding early treatment of febrile patients with neutropenia and cancer have been important issues and continue to be major challenges for clinicians. The use of nested PCR to make therapeutic decisions was studied. Sequential blood samples obtained from 42 patients with neutropenia and cancer were tested by nested PCR and culture. Instead of the empirical antifungal therapy strategy, amphotericin B treatment was initiated only for patients who had 2 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 30 publications
0
43
0
1
Order By: Relevance
“…The net clinical benefit afforded by PCR testing for IC could not be assessed. Although PCR results were available to clinicians attending the patient in the several studies performing PCR in real time, only one study directed patients' treatment by PCR results, showing that PCR-directed treatment was initiated 3 days (median; range, 0 to 8 days) before the diagnosis of candidemia by blood culture (44). None of the studies reported the effects of PCR on clinical outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The net clinical benefit afforded by PCR testing for IC could not be assessed. Although PCR results were available to clinicians attending the patient in the several studies performing PCR in real time, only one study directed patients' treatment by PCR results, showing that PCR-directed treatment was initiated 3 days (median; range, 0 to 8 days) before the diagnosis of candidemia by blood culture (44). None of the studies reported the effects of PCR on clinical outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of PCR-guided therapy in paediatric cancer patients, a reduced mortality was observed for febrile neutropenic patients with IFI and no fungal deaths were recorded in patients with PCR-negative febrile neutropenia. 35 Current management of IFI in haemato-oncology patients relies on empirical antifungal therapy. However, despite significant financial expenditure on antifungal therapy (around 33% of our SCT unit's total drug budget), this strategy is failing with mortality from IA remaining around 80-90%.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity has been highly variable, ranging from 50 to 100%, primarily because of differences in assay characteristics, types of patients evaluated, and certainty of IPA diagnosis (6, 8-10, 15, 19, 23). More recent studies have evaluated the use of real-time PCR assays applied to blood and BAL fluid (6,15,22); results suggest utility, although no standard assay platform has been used and no large study has been performed.…”
mentioning
confidence: 99%